Preliminary results of adapting the stepped care model for depression management in Vietnam - Do, Mai Tuyet; Nguyen, Tam Thanh; Tran, Huong Thi Thanh (Frontiers in Psychiatry, 2022)
Background Depression is the leading burden of mental disease, especially in low-and-middle-income countries like Vietnam. The Stepped Care Model is a promising approach to managing depression in the community with low resources. This is the first study that implemented the adapted Stepped Care Model for depression management in the Vietnamese context and evaluated the initial effectiveness of this community-based intervention in the Thai Nguyen community. Materials and methods A quasi-experimental study with a 3-month follow-up was conducted in 10 selected communes in Thai Nguyen province. The most important modifications in the Stepped Care Model for depression management were the screening focused on the high-risk individuals living in the community; the combination of 8-session group psychotherapy with animation activities at commune health stations (CHS); and using psychotherapy as first-line treatment. From August 2020 to January 2021, quantitative data were collected using the Patient Health Questionnaire-9, the Generalized Anxiety Disorder-7, and the Quality of Life Enjoyment and Satisfaction Questionnaire-Short Form. The descriptive analyses were performed to describe the demographic characteristics and the change in the questionnaires' mean score at the baseline and 3-month follow-up. Results A total of 1,891 people were approached in the community, of which 359 voluntary people met the study criteria and attended group psychotherapy. During group psychotherapy, the average PHQ-9 scores gradually decreased, and after the 8th session, this figure dropped by 2.65 times compared to the beginning. After 3 months, the percentage of the group with mild-moderate depression shrank from 95.5 to 9.3%, and there were no more severe cases. Moreover, life satisfaction increased by 32% and the anxiety level significantly dropped according to Q-LES-Q-SF and GAD-7 accordingly. Conclusion The preliminary results after 3-month follow-up showed that the Stepped Care Model with group psychotherapy at the CHS was promising to manage the depression in the community. This task shifting approach with limited resources should be further disseminated and studied for long-term effectiveness in low-and-middle-income countries like Vietnam.